Revisiting the archaeological investigations of rice domestication in China during 10,000–7,000 BP in a human behavioral context - Pan, Yan (Frontiers in Earth Science, 2023)
In East Asian archaeology, initial domestication and early dispersal of rice have continuously attracted scholarly interest in the recent decade, which has generated abundant new materials and revised opinions. This paper starts with a refreshed understanding of the domestication concept that emphasizes the dominant role of human behavior in the mutualistic relationship. A thorough review of the approaches to and data on reconstructing the rice story during 10,000–7,000 BP demonstrates the causally chained changes in phenotype, genotype, and human behavior in the establishment of domestication. Future studies will benefit from the revised paradigm, which has great potential to extract archaeological information to explain multiple mechanisms in rice domestication.